2013
DOI: 10.1002/phar.1218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pharmacologic Prophylaxis for Venous Thromboembolism in Patients with Chronic Liver Disease

Abstract: Pharmacologic VTE prophylaxis was associated with a decreased incidence of VTE in patients with CLD without an increased rate of bleeding and should be routinely considered on admission to the hospital. Patients with CLD and active malignancy, trauma or surgery during hospitalization, or history of VTE appear to be at highest risk of VTE and thus warrant pharmacologic prophylaxis. Prospective studies must validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
60
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 31 publications
3
60
2
Order By: Relevance
“…In contrast, other studies have shown a decreased incidence of VTE in patients with chronic liver disease given pharmacological prophylaxis (Barclay et al, 2013). In this latter study, multivariate logistic regression analysis identified risk factors for VTE amongst hospitalised cirrhotics as being active malignancy, trauma or surgery during hospitalization, or previous history of VTE (Barclay et al, 2013). This is in keeping with VTE studies from other hospitalised patient populations, and suggests that patients with cirrhosis with risk factors should not be precluded from receiving VTE prophylaxis.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…In contrast, other studies have shown a decreased incidence of VTE in patients with chronic liver disease given pharmacological prophylaxis (Barclay et al, 2013). In this latter study, multivariate logistic regression analysis identified risk factors for VTE amongst hospitalised cirrhotics as being active malignancy, trauma or surgery during hospitalization, or previous history of VTE (Barclay et al, 2013). This is in keeping with VTE studies from other hospitalised patient populations, and suggests that patients with cirrhosis with risk factors should not be precluded from receiving VTE prophylaxis.…”
supporting
confidence: 73%
“…Despite this, several recent studies of anticoagulation in those with advanced fibrosis or cirrhosis appear to demonstrate acceptable safety profiles. Studies of VTE prophylaxis in cirrhotics patients have demonstrated no significantly increased risk of bleeding with anticoagulation (Intagliata et al, 2014;Smith et al, 2013, Barclay et al, 2013. Reichert and colleagues did demonstrate that if the INR was greater than 1.5, then the risk of bleeding was increased, but this was only for bleeding classified as of minor severity (Reichert et al, 2014) and stratification by type of anticoagulation has demonstrated that unfractionated heparin results in a higher bleeding risk than low molecular weight heparin in cirrhotic patients (Intagliata et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reported rates range from 0.5% to 6.7% for incidence (Table 2), and from 0.6% to 4.7% for prevalence (Table 3), with higher values in patients with more severe liver disease [173] and in those with hepatocellular carcinoma [176]. Prophylaxis for VTE with anti-coagulants in patients with cirrhosis was shown to be safe and effective [177,178].…”
Section: Venous Thromboembolism In Liver Cirrhosismentioning
confidence: 99%
“…However, they confirm that a non-trivial proportion of CLD patients are prone to an increased thrombotic risk; this calls for studies aimed at the investigation of the risk stratification of patients according to the presence of patient-or disease-linked factors, and the opportunity of thromboprophylaxis in this setting. As in the general population, cancer, trauma or surgery during hospitalization and a previous history of VTE are strong predictors of VTE in CLD patients [19]; other factors associated with a higher risk of VTE in cirrhosis include black race, co-morbidities, malnutrition, central venous line placement, and diabetes [15,20]. Coagulopathy might protect patients from VTE [20]; yet, the INR measurement is not associated with the risk of VTE, and the risk does not decrease with worsening INR [14][15][16].…”
mentioning
confidence: 98%